High-Pressure Performance of Mixed-Conducting Oxygen Electrodes: Effect of Interstitial versus Vacancy Conductivity. Issue 13 (1st January 2016) - Railsback, Justin; Hughes, Gareth; Mogni, Liliana; Montenegro-Hernández, Alejandra; Barnett, Scott
Abstract : Electrochemical response was measured as a function of oxygen pressure pO2 up to 10 bar for four different mixed-conducting oxygen electrode materials, the oxygen-vacancy-conducting perovskites (Sm0.5 Sr0.5 )CoO3 (SSC) and (La0.6 Sr0.4 )(Co0.2 Fe0.8 )O3 (LSCF), and the interstitial-oxygen-conducting nickelates Pr2 NiO4 (PNO) and Nd2 NiO4 (NNO). The impedance spectroscopy (IS) measurements were done on symmetrical cells with either single-phase or two-phase infiltrated electrode structures. The polarization resistance decreased with increasing pressure in all cases, but the nickelates decreased more rapidly than the perovskites. It is proposed that this difference is a direct result of the different pO2 dependences of the defect concentrations – the oxygen vacancy concentration decreases with increasing pO2, whereas interstitial concentrations increase. In order to test this hypothesis, point defect concentrations were calculated for LSCF and NNO single-phase electrodes using the Adler-Lane-Steele model from electrochemical data and electrode microstructural parameters obtained by three-dimensional tomography. The results verified that the observed changes with increasing pO2 can be explained by reasonable decreases in LSCF vacancy concentration and increases in NNO interstitial concentration. These results suggest that nickelate electrodes can be advantageous for pressurized devices.